2008
DOI: 10.1021/ac702559s
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Use of Isotope Ratio Mass Spectrometry as a Tool for Discrimination of 3,4-Methylenedioxymethamphetamine by Synthetic Route

Abstract: Drug profiling, or the ability to link batches of illicit drugs to a common source or synthetic route, has long been a goal of law enforcement agencies. Research in the past decade has explored drug profiling with isotope ratio mass spectrometry (IRMS). This type of research can be limited by the use of substances seized by police, of which the provenance is unknown. Fortunately, however, some studies in recent years have been carried out on drugs synthesized in-house and therefore of known history. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 29 publications
(79 reference statements)
4
49
0
Order By: Relevance
“…16 For statistical purposes and in contrast to our one-dimensional approach the multivariate t-test named Hotellings-T 2 -test [18] using Statistica ® software was performed on all possible pairs of samples out of the 27 P2P samples, taking all three determined parameters simultaneously (δ 13 C V-PDB , δ 2 H V-SMOW and δ 18 O V-SMOW values) into account. Table 2 displays the essential results, the part left under the diagonal shows the T 2 -distances (except for samples [10][11][12] and the part right above the diagonal shows the associated Hotellings T 2 -test results (except for samples [10][11][12][13][14]. Only for 17 of all 351 possible pairs of samples the hypothesis that these samples are from the same source (here: batch) does not have to be rejected at 99% confidence level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 For statistical purposes and in contrast to our one-dimensional approach the multivariate t-test named Hotellings-T 2 -test [18] using Statistica ® software was performed on all possible pairs of samples out of the 27 P2P samples, taking all three determined parameters simultaneously (δ 13 C V-PDB , δ 2 H V-SMOW and δ 18 O V-SMOW values) into account. Table 2 displays the essential results, the part left under the diagonal shows the T 2 -distances (except for samples [10][11][12] and the part right above the diagonal shows the associated Hotellings T 2 -test results (except for samples [10][11][12][13][14]. Only for 17 of all 351 possible pairs of samples the hypothesis that these samples are from the same source (here: batch) does not have to be rejected at 99% confidence level.…”
Section: Resultsmentioning
confidence: 99%
“…To detect relations between different illegal drug labs IRMStechniques have been used for the characterization of the ATS products [7][8][9][10][11], but in casework you will often find only starting materials. Nevertheless it may be possible to link labs or substances by the isotopic data of these starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that IRMS for tracing MDMA to source is more complicated than expected, and that it might be hazardous to link MDMA samples based on 13C and 15N values alone. In 2008, Buchanan et al [15] reported a study inwhichMDMA samples were synthesized in-house by three preparative methods: reductive amination using Al/Hg amalgam, NaBH4, and Pt/H2. The authors carefully repeated each preparative method until six batches of each were obtained (18 in total).…”
Section: Irms Of Illicit Drugsmentioning
confidence: 99%
“…Profiling of seized and authentic drug samples for investigating sources, linkage (between sample groups, precursorproduct relationships, etc.) or discrimination purposes has been demonstrated for numerous synthetic substances including MDMA [21][22][23], MA [10][11][12][13]15,19,24,25] and more recently the designer drug mephedrone [16].…”
Section: Introductionmentioning
confidence: 99%